Genomic Distinctions of LA-MRSA ST398 on Dairy Farms From Different German Federal States With a Low Risk of Severe Human Infections - Lienen, Tobias; Schnitt, Arne; Hammerl, Jens Andre; Maurischat, Sven; Tenhagen, Bernd-Alois (Frontiers in Microbiology, 2021)
Methicillin-resistant Staphylococcus aureus (MRSA) have been found on German dairy farms and may be the cause of difficult-to-treat bovine mastitis. Considering the one health approach, MRSA might be transmitted from animals to humans raising the risk for severe infections. On 17 German dairy farms with a history of MRSA detection, MRSA strains were isolated from quarter milk, bulk tank milk and swab samples of calves, heifers, pigs and the environment. A selection of 33 isolates was analyzed using whole-genome sequencing and antimicrobial resistance testing. All detected MRSA strains were attributed to the livestock-associated sequence type 398. Methicillin-resistance was associated with the mecA gene in the SCCmec types IVa (7/33) or V (26/33). The MRSA strains across the German federal states showed large allelic differences indicating independent development and distribution. On one farm, a clonal MRSA isolate was widely spread among different animals and the milking equipment. Moreover, MRSA transmission between two dairy farms in one federal state seems to be likely. In depth studies indicated that the resistance gene prediction and phenotypic resistance are in good agreement. Twenty eight strains were determined to exhibit a non-wildtype phenotype (resistant) against up to seven antimicrobial substances with an overall resistance to β-lactams and tetracycline. Ten different phenotypic antimicrobial resistance patterns were found among the MRSA strains. The strains harbored a wide virulence gene repertoire, of which some of them are related to bovine mastitis. However, the isolates lacked typical human infection associated factors such as the immune evasion cluster genes, staphylococcal enterotoxin genes or Panton-Valentine leukocidin genes leading to the assumption for a low risk for severe human infections and foodborne diseases.